EXPOSURE RELATIONSHIP INFORMATION WITH THE LEVEL OF KNOWLEDGE AND BEHAVIOUR BSE IN WOMEN - Intan Mutiara Putri; Evi Nurhidayati; Djaswadi Dasuki (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2018)
The incidence of breast cancer by 40 per 100,000 women and will increase if there are one or more risk factors for breast cancer. Breast self-examination (BSE) is the early detection of breast cancer is the most widely recommended for every woman. The American Cancer Society recommends young women after the age of 20 to be screened with BSE every month. Nowadays there is a tendency of breast cancer experienced by women with age (15-20an). The purpose of this study to determine the relationship of information exposure to the level of knowledge of women about breast cancer and BSE behavior. Descriptive analytic research with cross sectional study sampled women aged 20-65 years living in the of Tegalrejo Yogyakarta total of 100 respondents. The sampling technique using a multistage random sampling. Bivariate data analysis using Chi - Square with significance level ρ 0.05 and CI 95% . The results of chi-square analysis of a significant relationship between exposure information with the level of knowledge about breast cancer and BSE with a p-value (0.021) and the OR value of 4.015. The results of chi-square analysis of a significant relationship between exposure information with BSE practice with a p-value (0.002) and the OR value of 3,3. In conclusion, hhere is a relationship between the exposure of information to the level of knowledge and breast self examanation behavior. Keywords: exposure information, knowledge, breast cancer, BSE